Urban heat island linkages with the landscape morphology - T. V. Ramachandra; Rajesh Singh Rana; S. Vinay; Bharath H. Aithal (Scientific Reports)
Abstract The landscape consists of a mosaic of interacting ecosystem elements, which maintain stability and aid in sustaining crucial services. Unplanned developmental activities leading to the transition of pervious surfaces into impervious/paved surfaces have significant implications for the urban climate, mainly through the phenomenon of urban heat islands (UHIs). Changes in landscape integrity could be quantified through land use (land cover) assessment and urban heat island effect through spatial computation of land surface temperature (LST). The current research uses multi-resolution remote sensing data to evaluate UHIs with landscape dynamics and assess the complex spatial interrelationships in heterogeneous urban landscapes at micro-levels. The composition of pervious and impervious surfaces at the micro-level plays a pivotal role in regulating thermal comfort. Landscape configuration at microlevels, predominantly barren (C1 class) and urban (C2 class) areas, constitute hotspots with higher temperatures. UHI was mapped through the urban hotspot and Urban thermal field variance index (UTFVI) analysis. Urban hotspot analysis shows the 15.41 km2 area in the city has a very high temperature. The study provides vital data-driven insights into the complex relationship between urban land use and LST at the micro-level that supports the decision-makers, stakeholders, and public officials in policymaking.